A CHARACTERISTICS OF PREDISPOSITION AND ABILITY OF FAMILY RESOURCES IN FAMILY DECISION FOR UTILIZING OF HEALTH SERVICES IN PUSKESMAS KELURAHAN PASIR KALIKI 2017 - Indra Karana Napitupulu; Babygia Carolina (Jurnal Kesehatan Prima, 2018)
Abstract: The precentage of utilization of health service in Puskesmas (Public Health Center) by the community is quite low only 30% nationally and 45.28% for Puskesmas UPT Pasir Kaliki Bandung. The objective study was to determine the characteristic of predisposition and ability of family resources in family decision for utilizing of health services in puskesmas kelurahan pasir kaliki. The research was descriptive. The population in the study was all communities around Puskesmas Pasir Kaliki Bandung by 95 respondents. The data were analyzed by univariate analysis. The findings in this study indicated that the greatest respondent who utilized health service was 41 respondents (low edication), 49 Respondents (on job). In addition respondents who had income below UMR (a minimum wage of people) and respondent who had health insurance and utilized health services was 61 respondents.Keywords: Education; Employment; Income; Health Insurance; Utilization of Health Services.